Evergreen Lights Sdn. Bhd. / Azrillaa Aziz ... [et al.] - Aziz, Azrillaa; Norbain, Norazreen; Muslaini, Sarini; Md. Salleh, Suhaila (Faculty of Office Management & Technology, 2003)
Our business is in the lighting field. We are specially focus on selling, supplying lights and electrical tools such as fan, door bell and bulb. We come out with the motto 'shining forever', which means we are very particular with customers, need and light up their life and give happiness to them through our products. We have so many bright ideas, if you need just one light, or want us to light your whole house and office. Our brilliant service team advises and cares from selection, recommendation, delivery installation and after sales service; we have someone you can count on so you'll never again be left in the dark.